2023
DOI: 10.1093/bjsopen/zrac167
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after hepatic resection of patients with hepatocellular carcinoma related to non-alcoholic fatty liver disease: meta-analysis

Abstract: Background Whether the safety and efficacy of hepatic resection differ between patients whose hepatocellular carcinoma (HCC) is related to non-alcoholic fatty liver disease (NAFLD) or has other aetiologies is unknown. A systematic review was performed to explore potential differences between such conditions. Methods PubMed, EMBASE, Web of Science, and Cochrane Library were systematically searched for relevant studies that rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…22 If their HCC is related to MAFLD, patients may have better survival and show major perioperative complications compared with patients with HCC of other aetiologies. 23 This study reveals that patients diagnosed with MAFLD-related HCC commonly exhibit preoperative comorbidities, including MetS and cardiac or kidney comorbidities, but CHB-related HCC tends to present a more severe liver disease. HCV-positive patients may exhibit both severe MetS and a more severe liver disease.…”
Section: Discussionmentioning
confidence: 83%
“…22 If their HCC is related to MAFLD, patients may have better survival and show major perioperative complications compared with patients with HCC of other aetiologies. 23 This study reveals that patients diagnosed with MAFLD-related HCC commonly exhibit preoperative comorbidities, including MetS and cardiac or kidney comorbidities, but CHB-related HCC tends to present a more severe liver disease. HCV-positive patients may exhibit both severe MetS and a more severe liver disease.…”
Section: Discussionmentioning
confidence: 83%
“…In a recent meta-analysis, cirrhosis was present in at least half of all the patients who underwent hepatic resection for HCC. 32 In contrast to intrahepatic cholangiocarcinoma (iCCA), extrahepatic cholangiocarcinoma is less frequently reported for patients with a background of liver cirrhosis. 33 In two large population studies, liver cirrhosis was found in 8–10% of iCCA patients compared with 4% of 539 patients who underwent a resection for pCCA.…”
Section: Discussionmentioning
confidence: 99%
“… 20 22 HCC patients usually have underlying chronic liver disease or cirrhosis caused by chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infection, alcoholic, or nonalcoholic steatohepatitis. 23 They thus always have early and late phase recurrence risk factors.…”
Section: Unanswered Questions Of Adjuvant Treatmentmentioning
confidence: 99%